2022
DOI: 10.1093/bjsopen/zrac107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interval between neoadjuvant chemoradiotherapy and surgery on disease recurrence and survival in rectal cancer: long-term results of a randomized clinical trial

Abstract: Background The optimal timing of surgery following chemoradiotherapy (CRT) is controversial. This trial aimed to assess disease recurrence and survival rates between patients with locally advanced rectal adenocarcinoma (LARC) who underwent total mesorectal excision (TME) after a waiting interval of 8 weeks or less (classic interval; CI) versus more than 8 weeks (long interval; LI) following preoperative CRT. Methods This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…19 Terzi et al 23.6% vs. 12% p = 0.02; Akgun: 18.6% vs. 10% p = 0.027). 45,46 Terzi and colleagues found no difference in morbidity between the two groups but did find a significant increase in sphincter-sparing operations in the shorter interval group (85.6% vs. 74%; p = 0.016). 45 Five meta-analyses investigated the relationship between RSI and tumor response by pooling many of the aforementioned studies.…”
Section: Question 1: Does a Longer Rsi Improve Rates Of Pcr And Does ...mentioning
confidence: 96%
See 4 more Smart Citations
“…19 Terzi et al 23.6% vs. 12% p = 0.02; Akgun: 18.6% vs. 10% p = 0.027). 45,46 Terzi and colleagues found no difference in morbidity between the two groups but did find a significant increase in sphincter-sparing operations in the shorter interval group (85.6% vs. 74%; p = 0.016). 45 Five meta-analyses investigated the relationship between RSI and tumor response by pooling many of the aforementioned studies.…”
Section: Question 1: Does a Longer Rsi Improve Rates Of Pcr And Does ...mentioning
confidence: 96%
“…19 Akgun and colleagues, which randomized patients to RSI of short (4-8 weeks) versus long (8-12 weeks) showed long RSI patients had lower rates of distant metastases (19% vs. 31%) but no difference in local recurrence, 5-year DFS, or 5-year OS. 46 Lefevre and colleagues, who reported in their GRECCAR-6 trial that short (7 weeks) versus long (11 weeks) RSI did not affect rates of pCR, showed no difference in local or distant recurrence and 3-year OS and DFS. 65 Similarly, four metaanalyses did not find a difference in OS with longer intervals between radiation and surgery.…”
Section: Question 2: Do Increased Rates Of Pcr Translate To Improved ...mentioning
confidence: 97%
See 3 more Smart Citations